Application of incomplete similarity theory for estimating maximum shear layer thickness of granular flows in rotating drums - Cheng, Nian-Sheng (2012)
Granular flow in a rotating drum provides a convenient system for investigating mixing, segregation and general properties of granular materials. This study is concerned with the maximum thickness of the flowing surface layer observed at the rolling regime. A scaling relation is first derived with the consideration of incomplete similarity associated with the drum-particle size ratio and the Froude number. Calibration is then carried out with published laboratory data, which were collected for the case of rotating drums half-filled with glass beads. The scaling relation is also compared with other kinds of datasets, showing good agreement and possibilities of the proposed approach to be further extended to more complex cases.